Strategi Penyuluhan di Kawasan Konservasi (Kasus Taman Nasional Kepulauan Togean) - Muhd Nur Sangadji; Sumardjo Sumardjo; Pang S Asngari; Soenarmo H Soewito (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2011)
The aim of this research are (1) To describe the factors influences the community participation on management of Togean Island National Park. (2) To analyze the role of extension and it’s correlation to the community participation. (3). To formulate an extension strategy to increase the community participation on management of Togean Island National Park. The research was conducted in Togean Island National Park in Central Sulawesi on August to Septembre 2008 and March to April 2009. Five variables are used to measure the community participation by using Structural Equation Model (SEM) and LISEREL 8.30 sofware. Those variables are internal characteristic, extension process, eksternal factor, community capacity and community participation. The result of research shown that extension proccess have a significant effect on the community capacity. Community capacity have a significant effect to the community participation on management of Togean Island National Park. The strategy that can be used to increase the community participation is to improve the process of extension. Keywords: extension, community participation and national park.